An interactive mobile three-dimensional virtual laboratory for learning ear anatomy - Atina Putri; Fahma Waluya Rosmansyah; Chessa Nur Triejunita; Yuda Sukmana; Nyilo Purnami; Sakina Sakina; Yuni Sari Amalia; Yusep Rosmansyah (Smart Learning Environments)
Abstract The increasing popularity of mobile devices as alternative tools for learning has led to the adoption of virtual laboratory simulation (VLab) to enhance practical learning experiences. This paper introduces an interactive mobile learning application designed to facilitate medical students in learning ear anatomy using a three-dimensional model. Furthermore, this study examines students’ perceptions of VLab and its impact on the learning process, as evidenced by their performance. The research involved a total of 40 medical and engineering students who were enrolled in anatomy and physiology courses. A cross-over repeated measures design was conducted to compare students’ experiences with both types of learning methods: conventional and VLab. To analyze students’ perceptions of VLab, a five-point Likert scale comprising 22 question items was utilized based on the hedonic-motivation system adoption model, which includes seven variables: heightened enjoyment, behavioral intention to use, perceived usefulness, curiosity, control, perceived ease of use, and focused immersion (FI). Additionally, students’ performance data were collected through the pre-test, mid-test, and post-test. The results of quantitative statistical analysis indicated that VLab generally fulfilled students’ perceptions. Moreover, the findings revealed that the combination of conventional learning approaches and VLab positively enhanced students’ learning performance, as demonstrated by improvements in their scores.